2007
DOI: 10.1097/phm.0b013e31802b8937
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity and High Blood Pressure in Veterans with Spinal Cord Injuries and Disorders

Abstract: Obesity and high BP rates were lower for veterans with SCI&D than the general population. However, because BMI underestimates body adiposity in SCI&D, obesity is likely a much more prevalent problem in this population and warrants attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 16 publications
5
90
1
Order By: Relevance
“…10 However, increasing exercise and maintaining an appropriate lean body-mass percentage are significant challenges for patients with SCI/D. 11 In addition, injury to the spinal cord itself has a direct impact on the regulation of blood pressure. Physicians generally contend with conditions of low blood pressure including orthostatic hypotension, adaptive myocardial atrophy, bradyarrhythmia, reduced peripheral vascular resistance and venous pooling.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, increasing exercise and maintaining an appropriate lean body-mass percentage are significant challenges for patients with SCI/D. 11 In addition, injury to the spinal cord itself has a direct impact on the regulation of blood pressure. Physicians generally contend with conditions of low blood pressure including orthostatic hypotension, adaptive myocardial atrophy, bradyarrhythmia, reduced peripheral vascular resistance and venous pooling.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our research, there is no study available to compare BP in complete and incomplete patients. However, a possible reason for that is elevation due to autonomic dysreflexia at the time BP was recorded [11]. On the other hand, there remains a relationship between increased BMI levels and higher BP [11].…”
Section: Sabour Et Al Cardiometabolic Risk Factors In People With Scimentioning
confidence: 99%
“…Persons with SCI have significantly less fat-free mass and greater fat mass than nondisabled persons [6]. Despite altered body composition, body mass index (BMI) has been a poor and inconsistent predictor of CHD in persons with SCI [11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, more than half of patients with SCI are obese or overweight, leading to an increased risk for both SDB and cardiac diseases. 2 Our group has been studying SDB among SCI patients, and, we have found that SDB, defined by the apnea-hypopnea index ⩾ 5 events per hour, was present in 77% of chronic SCI patients, with rates higher among those with cervical compared with thoracic injuries (93% vs 55%, respectively, Po0.05). 3 One in four cervical SCI had Cheyne-Stokes respiration pattern during their overnight laboratory sleep study, and one in five had hypertension or cardiac disease.…”
mentioning
confidence: 94%